1997
DOI: 10.1161/01.res.81.3.423
|View full text |Cite
|
Sign up to set email alerts
|

Expression Pattern of Connexin Gene Products at the Early Developmental Stages of the Mouse Cardiovascular System

Abstract: The synchronized contraction of myocytes in cardiac muscle requires the structural and functional integrity of the gap junctions present between these cells. Gap junctions are clusters of intercellular channels formed by transmembrane proteins of the connexin (Cx) family. Products of several Cx genes have been identified in the mammalian heart (eg, Cx45, Cx43, Cx40, and Cx37), and their expression was shown to be regulated during the development of the myocardium. Cx43, Cx40, and Cx45 are components of myocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
140
2
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(161 citation statements)
references
References 65 publications
15
140
2
4
Order By: Relevance
“…S3) was used to identify Irx3-expressing myocytes isolated from the proximal VCS. In agreement with the gradual enrichment of Cx40 to VCS and down-regulation of Cx43 in these cells during development (22), quantitation of Cx plaque expression between cell pairs showed that the majority of cells from the proximal VCS (Irx3::EGFP + ) expressed Cx40 between cells ( Fig. 1 K and L).…”
Section: Resultssupporting
confidence: 76%
“…S3) was used to identify Irx3-expressing myocytes isolated from the proximal VCS. In agreement with the gradual enrichment of Cx40 to VCS and down-regulation of Cx43 in these cells during development (22), quantitation of Cx plaque expression between cell pairs showed that the majority of cells from the proximal VCS (Irx3::EGFP + ) expressed Cx40 between cells ( Fig. 1 K and L).…”
Section: Resultssupporting
confidence: 76%
“…In the uterus, as in cardiac muscle and vascular smooth muscle, functional gap junctions promote the development of coordinated oscillatory contractions (Garfield and Hayashi, 1981;Christ et al, 1993;Oyamada et al, 1994;Watts et al, 1994;Tsai et al, 1995;Delorme et al, 1997). Lindane inhibits gap junction communication between myometrial cells in culture and inhibits spontaneous oscillatory contractions of uterine strips in muscle baths, as shown previously Loch-Caruso, 1995, 1999; and confirmed in the present report.…”
Section: Discussionsupporting
confidence: 89%
“…These left/right ventricular differences are transient and occur during either activation or downregulation of gene expression. Examples of genes showing left/right differences as they are activated include MCK, which is expressed in the compact myocardium of the RV at E12.5, prior to expression throughout the heart (Hasselbaink et al, 1990;Lyons, 1994), and connexin 40 which is expressed in the LV but not the RV at E10.5, prior to expression in both ventricles at E13.5 (Delorme et al, 1997). Genes which have been shown to be asymmetrically expressed in the ventricles as they are being downregulated include MLC3F, which is expressed (as transcript but not protein) at a lower level in the RV than the LV between E10.5 and E12.5 (Kelly et al, 1998), and ANF which is expressed in the trabeculae of the LV at E14.5 (Zeller et al, 1987); both genes continue to be transcribed in the atria.…”
Section: Discussionmentioning
confidence: 99%
“…Further regionalisation of transcriptional potential in the heart has been documented for a number of transgenes which are ex- pressed in either the right or left ventricular or atrial myocardium: reporter genes controlled by MLC3F or ␣-cardiac actin regulatory sequences are expressed in the LV and right atrium (RA) (Kelly et al, 1995;Biben et al, 1996), whereas MLC2V and desmin regulatory elements confer RV and OFT expression (Ross et al, 1996;Kuisk et al, 1996). Such asymmetric expression has not been documented for most endogenous cardiac genes, although some, such as M-creatine phosphokinase (MCK), connexin 40, and MLC3F show left/right differences in the ventricles as they are being activated or downregulated (Lyons, 1994;Delorme et al, 1997;Kelly et al, 1998). In addition, the bHLH transcription factors dHAND and eHAND are expressed in the right and left ventricles respectively from early stages of heart development (Biben and Harvey, 1997;Srivastava et al, 1997).…”
Section: Introductionmentioning
confidence: 99%